Leaking letters: The case of Harriot’s report and six letters of englishmen - Mohammed Ghazi Alghamdi (Cogent Arts & Humanities, 2022)
This paper attempts a new historicist reading that scrutinizes the nature of Thomas Harriot’s “A Brief and True Report of the New Found Land of Virginia” by juxtaposing it with six letters written after the publication of Harriot’s Report in 1588. To step outside Harriot’s text as a travel narrative, this paper examines how his report, which may have contributed to the migration of the English to New England, and how six personal letters ranging from 1623 to 1639—three by Richard Frethorne, one by John Baldwin, another by George Calvert, and the last one by an anonymous writer—challenge Harriot’s account as imaginary and redefine the migration journeys to New England. The findings of this paper may be familiar to scholars of transatlantic literature; however, its significance lies in its methodology of comparing Harriot’s report to six personal letters, thus asserting the prominence of reading letters against travel narratives. In doing so, personal letters, as a genre, can be a valuable apparatus to study the nexus between any text (literary foreground) and history (political/social background)—personal letters being the historical accounts that correspond to other texts.